Spatial Distribution and Provenance of Detrital Minerals of Surface Sediment in the Okhotsk Sea - Wang, Kunshan; Shi, Xuefa; Zou, Jianjun; Liu, Yanguang; Yao, Zhengquan; Gorbarenko, Sergey Alexandrovich (Frontiers in Earth Science, 2021)
The Okhotsk Sea is a distinctive marginal sea in the northwestern Pacific Ocean, which is characterized by the prevalence of seasonal sea ice in winter. Sediment is sourced from the around region through sea ice transportation, rivers input, and volcanic eruptions. Surface sediments of the Okhotsk Sea shelf vary greatly in grain size, and the sand content is generally high, which is conducive to source-to-sink studies using ice-rafted detritus (IRD),detrital minerals and single mineral geochemistry methods. In this paper, the 63–125 μm grain size fraction was selected for the detrital minerals analysis of surface sediments (top 0–10 cm) from 58 sediment stations and 15 stations samples has been chosen for garnet chemistry. These stations are mainly located in the south central Okhotsk Sea. The distribution and composition of the heavy minerals are influenced by material derived from the Amur River, the north shelf (Okhotsk-Chukotka volcanic belt), Sakhalin Island, the Kamchatka Peninsula, and the Kuril Islands. The detrital mineral results show that hornblende, epidote and garnet are terrigenous material indicators. High contents of fresh hypersthene can be used as an indicator of volcanic eruption materials. And high content of abraded hypersthene can be used as an indicator of Okhotsk-Chukotka volcanic materials. In the northern Okhotsk Sea, the southward moving sea ice produced in Sakhalin Bay collides with the sea ice produced off the east coast of Sakhalin Island, which causes the sea ice to accumulate to the southeast. This results in the deposited ice-rafted debris having a southeastward facing fan shape, and the geochemical analysis of the garnet supports this conclusion. From west to east, the amount of material from Sakhalin Island gradually decreases, while the amount of material from the Amur River and Chukchi-Kamchatka increases.